2021
DOI: 10.2147/ott.s322710
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Apatinib for Elderly Patients with Advanced or Metastatic Gastric Cancer After Failure of at Least First-Line Chemotherapy: A Multi-Center, Single-Arm, Phase II Study

Abstract: Background Apatinib improves progression-free survival and overall survival with an acceptable safety profile in Chinese patients with chemotherapy-refractory advanced or metastatic gastric cancer. However, the efficacy and safety of apatinib are unclear for elderly patients. This study was undertaken to prospectively investigate the efficacy and safety of apatinib for elderly patients with unresectable advanced or metastatic gastric cancer, who experienced progression to at least one lines of che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…The incidence and severity of AEs in our study were generally consistent with the known safety profile of apatinib. The most common AEs were hypertension, fatigue, hand-foot syndrome, and nausea, which were also among the most frequently reported apatinib-related AEs in previous studies in GC, lung cancer, breast cancer, and ovarian cancer (8,(16)(17)(18)(19)(20)(21)(22)(23)(24). No new safety signals were observed.…”
Section: Discussionmentioning
confidence: 70%
“…The incidence and severity of AEs in our study were generally consistent with the known safety profile of apatinib. The most common AEs were hypertension, fatigue, hand-foot syndrome, and nausea, which were also among the most frequently reported apatinib-related AEs in previous studies in GC, lung cancer, breast cancer, and ovarian cancer (8,(16)(17)(18)(19)(20)(21)(22)(23)(24). No new safety signals were observed.…”
Section: Discussionmentioning
confidence: 70%
“…In 2014, the drug was approved and listed in China to treat patients with advanced gastric adenocarcinoma or gastric esophageal junction adenocarcinoma who had progressed or relapsed after receiving at least two kinds of systematic chemotherapy. Currently, phase II/III clinical trials are being conducted in China, and good clinical results have been achieved in the treatment of GI tumors (20)(21)(22)(23).…”
Section: Figurementioning
confidence: 99%
“… 126 In 2014, apatinib was approved in China for two or more advanced, or metastatic, GCs that cannot be treated with prior chemotherapy and is considered the standard third-line treatment in China. 127 Apatinib showed positive results in the Chinese GC population, leading to official approval for clinical use. However, the phase III clinical trial ANGEL, which is currently studying apatinib in a Western cohort, showed disappointing first results presented at the 2019 ESMO Annual Meeting.…”
Section: Clinical Evidence For Anti-angiogenic Therapy In Gastric Cancermentioning
confidence: 99%
“…126 In 2014, apatinib was approved in China for two or more advanced, or metastatic, GCs that cannot be treated with prior chemotherapy and is considered the standard third-line treatment in China. 127 Apatinib showed positive results in the Chinese GC population, leading to official approval for clinical use.…”
Section: Clinical Evidence For Anti-angiogenic Therapy In Gastric Cancermentioning
confidence: 99%